Impact of Topical v/s Systemic Steroids on Regaining Olfaction in Post Covid-19 Patients; A Randomized Controlled Trail - Usama Naveed Cheema, Shahi Zeb, Laiba Irfan, Mirza Zeeshan Sikandar, Syed Arslan Ashraf, Khalid Munir (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Covid-19 is a spectrum of infection not only causing fever and respiratory changes but including alteration in chemosensory functions including; olfactory dysfunction and gustatory dysfunction. In covid-19, olfactory dysregulation could be treated with either systemic steroids or with topical steroids. Objective: To assess and compare role of systemic and topical steroids in regaining normal olfactory functions. Materials & Methods: A Randomized control trial was conducted at Central Park Teaching Hospital Lahore after getting ethical approval and prior written informed consent from participants. A total of 35 patients were recruited were segregated into two groups; Group 1 who were treated with topical steroids (n=17) and Group 2 who were given and treated with systemic steroids (n=18). Time frame of regain of olfaction was compared between the groups using Mann Whitney U test. A p value less than 0.05 was considered as significant. Results: A total of 35 participants participated in this randomized controlled trial who were segregated into two groups with the mean ages of 47.12 + 11.94 and 43.72 + 13.74 with no significant mean difference. On appliance of Mann-Whitney U test in Group 1 and group 2 (52 + 39 v/s 4 + 2) it was observed that systemic steroid patients regain olfaction earlier as compared to group 1 (topical steroids) with the p value of .0001. Practical implication: Systemic Steroids will help in prompt regaining of normal olfaction and should be part of COVID-19 infection management. Conclusion: Olfaction management till the regaining of normal olfactory functions should be part of covid-19 management and role of steroids in crucial yet unavoidable. Systemic steroids play a key role in early regain of normal olfactory response so should be encouraged under the physician observation. MeSH Words: Covid-19, olfaction, steroids, respiratory disorders, randomized controlled trial.